Mosquito Detection using Deep Learning based on Acoustics - Bist, Ankur Singh; Mursleen, Mohd; Mohan, Lalit; Pant, Himanshu; Das, Purushottam (The journal of contemporary issues in business and government, 2021)
Deep learning based techniques are becoming popular because of its stability. Success of voice analytics can be seen because in various applications like alexa, siri etc. Behind the scenes main concept is to generate and analyze features so that it can be applicable in real world. In this paper we are proposing a deep learning based pipeline for mosquito detection. Hardware integration with software techniques will create device that can meet need of end user. Further AI Nano Jetson and flying machine are used to complete the end goal.